The actions/artifacts of historical agents as expressions of rational, purposive thought: R. G. Collingwood's own 'absolute presupposition'. - Juric, Adrian R. (University of Ottawa (Canada), 1992)
The purpose of this thesis will be to defend R. G. Collingwood's claims about the existence, and the significance, of Absolute Presuppositions. This defense will fall into three main sections. In the first section, I will provide a detailed critical examination of the methods of metaphysical analysis prescribed by Collingwood for uncovering Absolute Presuppositions in the first place: the 'logic of question and answer'. In the second section, I will draw attention to what I take to be the main problem with the Essay on Metaphysics: the fact that this method of metaphysical analysis is never applied in any systematic, thoroughgoing way. In the third and final section of the thesis I will try and remedy this situation. I will do so by applying the method of analysis prescribed by Collingwood to his own historical inquires--specifically, those contained in Roman Britain. This application will produce two important results. (1) It will provide a much-needed demonstration of Collingwood's method in an applied setting. (2) It will reveal the operation of one of Collingwood's own absolute presuppositions, viz. the presupposition that the actions of historical agents and the artifacts left by them are expressions of rational, purposive thought. (Abstract shortened by UMI.)
Keywords: Philosophy.